2017
DOI: 10.1128/jcm.00345-17
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Galactomannan Antigen Test in Serum and Bronchoalveolar Lavage Fluid Samples from Patients with Nonneutropenic Invasive Pulmonary Aspergillosis

Abstract: The objective of this study was to compare the diagnostic value of galactomannan (GM) detection in bronchoalveolar lavage fluid (BALF) and serum samples from nonneutropenic patients with invasive pulmonary aspergillosis (IPA) and determine the optimal BALF GM cutoff value for pulmonary aspergillosis. GM detection in BALF and serum samples was performed by enzyme-linked immunosorbent assay (ELISA) in 128 patients with clinically suspected nonneutropenic pulmonary aspergillosis between June 2014 and June 2016. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
131
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(145 citation statements)
references
References 21 publications
11
131
0
3
Order By: Relevance
“…In general, BAL GM index ≥ 1.0 showed a higher specificity for both fungus ball and aspergilloma detection but a decreased sensitivity compared to BAL GM index ≥ 0.5. Recently, the cut‐off value for BAL GM detection by ROC curve analysis was reported a range of 0.5‐1.18 in non‐neutropenic patients with pulmonary aspergillosis including aspergilloma 7,24 . In this present study, the statistical analysis of the sensitivity, specificity, PPV, NPV, correlation coefficient, likelihood ratios and AUC for GM detection (index ≥ 0.5) in BAL samples from old PTB patients with fungus ball also showed a significant correlation.…”
Section: Discussionsupporting
confidence: 66%
“…In general, BAL GM index ≥ 1.0 showed a higher specificity for both fungus ball and aspergilloma detection but a decreased sensitivity compared to BAL GM index ≥ 0.5. Recently, the cut‐off value for BAL GM detection by ROC curve analysis was reported a range of 0.5‐1.18 in non‐neutropenic patients with pulmonary aspergillosis including aspergilloma 7,24 . In this present study, the statistical analysis of the sensitivity, specificity, PPV, NPV, correlation coefficient, likelihood ratios and AUC for GM detection (index ≥ 0.5) in BAL samples from old PTB patients with fungus ball also showed a significant correlation.…”
Section: Discussionsupporting
confidence: 66%
“…The updated Infectious Diseases Society of America (IDSA) guidelines recommend bronchoalveolar lavage fluid (BALF) galactomannan (GM) and aspergillus IgG antibody testing for diagnosing chronic forms of pulmonary aspergillosis. Our previous work has confirmed that the BALF galactomannan (GM) testing offers diagnostic value [5]. However, invasiveness, numerous false positives, and the lack of standardization suggest that better biomarkers for diagnosing aspergillosis are needed, especially for the early diagnosis of invasive pulmonary aspergillosis (IPA) and subacute invasive aspergillosis (SAIA) in non-neutropenic patients.…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent systematic review, Zou et al 21 revealed that at an optimal cut‐off index of 1.0, BALF GM test has a higher pooled sensitivity than PCR and serum GM tests, indicating that BALF GM test could be a useful adjunct in the diagnosis of proven and probable IA. Moreover, BALF GM test is valuable for earlier diagnosis of invasive pulmonary aspergillosis (IPA) in non‐neutropenia patients 22 . However, false‐positive results of BALF GM test may occur in lung transplant patients and in those only colonised with Aspergillus 19 .…”
Section: Gm As a Biomarker For Invasive Aspergillosis Diagnosismentioning
confidence: 99%